The Application of Storytelling Technique on Students’ Speaking Ability at SMP Negeri 2 Tompaso - Ratu, Astrid; Liando, Nihta V. F; Rombepajung, Paula A. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
The goal of the research is to determine whether or not storytelling can help students become more proficient speakers. The researcher delimits the study on developing students’ speaking ability using storytelling techniques and be limited to the teacher and student interaction with three material to test for collection the data. This is a quantitative research, and procedure through preexperimental design with one group pretest and posttest. The data collect using Oral test which one to administer the pre-test. This test will determine the extent of the students' understanding as well as the way in which they pronounce the selected story's words and sentences prior to the intervention. Each student must pronounce the provided words and sentences on the test in order to receive the score they receive. The analysis of the data yields the following conclusion: the posttest mean score is 65.40, which is higher than the pretest mean of 32.90. This finding suggests that using the storytelling technique to help students become more proficient speakers is beneficial.